FINITE ELEMENT ANALYSIS OF MODULAR FIXTURES STRUCTURE STIFFNESS ON AXIAL DIRECTION - Dragoş Florin CHITARIU (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2015)
The paper presents a study of modular structure rigidity formed of base plates and locator/ body fixtures modules, resulting structures with similar dimensions but with different modules using finite element analysis, based on a series of experimental results, in order to correlate the results. The highlighted deformation indicates the possibility of axial irregular deformation under axial uniform deformation may lead to orientation and position deviations of the workpiece during clamping and machining (angular and linear displacement of the measurement base).